MEWUJUDAN PELAJAR PANCASILA DENGAN MENGINTEGRASIKAN KEARIFAN BUDAYA LOKAL DALAM KURIKULUM MERDEKA - Shinta Dwi Handayani; Ari Irawan; Chatarina Febriyanti; Gita Kencanawaty (Ilma Jurnal Pendidikan Islam, 2022)
This research aims to see how an independent curriculum implemented with local cultural wisdom is able to realize the profile of Pancasila students. The method used in this research activity is qualitative description by using interviews, observation and documentation. In addition, literature studies from various journals are used as a reference to see the development of the implementation of the independent curriculum. The results of this research are that it is very relevant that local wisdom culture is integrated with the independent curriculum to create a profile of Pancasila students.